Phytochemical Analysis And Antitubercular Potential Of All Spice (Journal of Pharmaceutical Negative Results, 2023)
Phytochemical analysis of plant products took a distinct place in plant biochemistry as well as organic chemistry in recent years. Now days it is one of the challenges of phytochemistry is to carry out all the above operations in small amounts of material. Pimenta dioica Linn also called as “All-spice” contain various secondary metabolites with great potentials. The present study investigates the qualitative and quantitative analysis of the major phytochemicals from fruits of medicinally important plant Pimenta dioica with their antitubercular potential. The findings from quantification and phytochemical screening showed the presence of alkaloids, flavonoids, Phenols, proteins, amino acids, saponins, tannins, terpenoids and glycosides. Further, the study findings revealed that ethanolic extract of fruits extract was found to more competent to isolate phytocomponents from plant. A Microplate based Alamar blue assay has been applied to search for novel antimicrobials to treat tuberculosis. The selective ethanolic phytochemicals from fruits of Pimenta dioica confirms the presence antitubercular potential.